COMPARISON OF REGIONAL TAXES, GENERAL ALLOCATION FUNDS, SPECIAL LOCATION FUNDS AND CAPITAL EXPENDITURE IN REGION I SUMATERA - Ana Annisa; Sri Wahyuni; Azka Rizkina (CV. Radja Publika, 2025)
The purpose of this study is to determine the comparison of regional taxes, general allocation funds, special allocation funds and capital expenditures in the regional region I of Sumatra. In this study, a quantitative research type was used to examine certain populations and samples, data analysis using statistical equations with the aim of testing the established hypothesis. The population or sample in this study was Aceh Province and North Sumatra Province, which are located in region I of Sumatra with data taken 15 years each from the two provinces. In this study, secondary data types were used. The results of this study showed that regional taxes, general allocation funds, special allocation funds and capital expenditures differed between Aceh Province and North Sumatra Province. Regional taxes in Aceh Province and North Sumatra Province have significant differences. General allocation funds in Aceh Province and North Sumatra Province also have significant differences. And special allocation funds in Aceh Province and North Sumatra Province have significant differences. As well as capital expenditures in Aceh Province and North Sumatra Province there are significant differences.